Genotype–phenotype variability of retinal manifestation in primary hyperoxaluria type 1. (4th March 2018) - Dulz, S.; Bigdon, E.; Atiskova, Y.; Schuettauf, F.; Cerkauskiene, R.; Oh, J.; Brinkert, F.
ABSTRACT: Background: Primary hyperoxaluria type 1 (PH1) is a rare congenital metabolic disorder of the glyoxylate pathway, which manifests with nephrocalcinosis, urolithiasis, and end-stage renal failure (ESRD) as well as deposition of oxalate crystals within ocular tissues. This report demonstrates classical ocular features of PH1 of the posterior pole and furthermore highlights the ocular genotype–phenotype variability among siblings with identical compound heterozygous alanine-glyoxylate aminotransferase (AGXT) mutations. Materials and Methods : Two siblings, an 8-year-old boy and an 18-year-old girl, with genetically confirmed AGXT mutation (c.364C>T (p.R122X) and c.33dupC), but different renal phenotype underwent an ophthalmic examination, including slit-lamp examination and funduscopy as well as optical coherence tomography (OCT), near-infrared autofluorescence (NIA), and microperimetry examination. Results : The 8-year-old boy presented with a best-corrected visual acuity (BCVA) of 20/630. Fundus examination revealed bilateral, whitish oxalate deposits and prominent fibrotic macular scars. OCT imaging illustrated hyperdense deposits in all retinal layers and the choroid and the vitreous body along with a prominent dome-shaped macular fibrosis. NIA imaging outlined macular retinal pigment epithelium (RPE) atrophy with panretinal hyperreflective material. Bilateral symptomatic epiphora was putatively due to bilateral depositions of palpable nodular oxalate deposits at the level of the lacrimal sac. In contrary, the 18-year-old sister presented without any signs of ocular oxalate deposition and a BCVA of 20/20. Conclusions : PH1 is potentially accompanied with a considerable decline in visual acuity due to macular scaring and fibrosis, whereas a profound variability of ocular manifestations can be observed in PH1 patients with identical genotypes.